A Pattern of Empowerment of Traditional Values Mawah as a Model of Poverty Alleviation Based on the Supply Chain Strategy - Nelly, Nelly; Rahmi, Rahmi; Mahdani, Mahdani; Ismail, Djuraidin (International Journal of Supply Chain Management, 2020)
Abstract- Mawah customary practice is very popular in Aceh so that with the customary practice of this Mawah much help the lives of the poor. This study aims Birthing a model implementation mawah customary practice in the district of Kuta Baro, Aceh Besar distric based on the supply chain strategy. Generate a poverty reduction strategy based on local wisdom through customary practices mawah Kuta Baro Sub-district, Aceh Besar District. Poverty is a key issue in Indonesia's development and economic quality is the key to the problem. The main problem in alleviating poverty in Indonesia today is related to the fact that economic growth is not spread evenly throughout Indonesia, as evidenced by the high income disparity between regions. The potential in the agricultural sector is very large, but most of the many farmers are among the poor and it is very ironic in Indonesia. The practice of indigenous mawah in Kecamatan Kuta Baro has been going on for generations, the practice that the community is doing is paddy fields, where the owners of the rice fields entrust their fields to be cultivated by the people who need the rice fields to help meet their daily needs where this practice can be one strategies for poverty alleviation in Kuta Baro Aceh Besar sub-district. This study aims to give birth to a pattern of empowerment of traditional values mawah as a model of poverty alleviation. The location of this research is in Kuta Baro sub-district, Aceh Besar district, with population in 5 (five) mukim areas. The number of samples is 5 (five) villages representing each mukim. Collected data processing will be processed with the